Increase in the dynamic force transmitted by a mass spring damper system model. - Hernandez, Jaime Y. Jr (Philippine Engineering Journal)
The analysis of a mass spring damper system model shows a variation in the derived equation of the dynamic force transmitted compared to that of the applied force when the model is subjected to a sinusoidal displacement load. Upon substitution of values, the force time history plot shows a possible increase in the transmitted force. This can be seen as the tilting of the principal axis of the corresponding hysteresis loop which implies an increase in stiffness. This phenomenon was observed during the testing of the Load Distribution and Energy dissipating (Lded) device. The Lded device is effective in transmitting structure generated forces while dissipating a portion of the energy induced during earthquakes.